2019
DOI: 10.1017/s1049023x18001206
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Provision During a Sporting Mass Gathering: A Structure and Process Description of On-Site Care Delivery

Abstract: IntroductionMass gatherings such as marathons are increasingly frequent. During mass gatherings, the provision of timely access to health care services is required for the mass-gathering population, as well as for the local community. However, the nature and impact of health care provision during sporting mass gatherings is not well-understood.PurposeThe aim of this study was to describe the structures and processes developed for an emergency health team to operate an in-event, acute health care facility durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Our results support those of other studies where findings suggested the provision of onsite healthcare that includes highly skilled clinicians (not simply a first aid post) ensures delivery of care for both acute physiological conditions and mental illness 14 and reduces impacts on local EDs. 23,24 It should be noted that no economic evaluation of this care model was undertaken and so its relative 'value' remains unclear.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results support those of other studies where findings suggested the provision of onsite healthcare that includes highly skilled clinicians (not simply a first aid post) ensures delivery of care for both acute physiological conditions and mental illness 14 and reduces impacts on local EDs. 23,24 It should be noted that no economic evaluation of this care model was undertaken and so its relative 'value' remains unclear.…”
Section: Discussionsupporting
confidence: 90%
“…Given the nature of the Schoolies event, where thousands of school-leavers gather to celebrate, the already busy EDs could be negatively impacted by surges in patient numbers. 14 Since the late 1990s, the Queensland Ambulance Service (QAS) instigated an evening In-Event Health Service (IEHS) for the Schoolies MGE. Such 'Pop-up' health services are designed to cope with an influx of patients linked to mass gatherings or health crises/pandemics.…”
Section: Key Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was evident with the 420 cases seen within the facility over the 7‐day period with only a small proportion (0.03%, 0.3/1000) requiring transfer by ambulance to the ED. As noted in other out‐of‐hospital ED avoidance strategies the multi‐disciplinary and inter‐agency staffing configuration likely contributed to this success; however, accompanying comprehensive structure and process evaluations of this and other EHS located at MGEs is required to understand this further. Additional public messaging to young adults attending Schoolies may be considered by event planners to create awareness of the EHS which may further minimise the impact on the ED …”
Section: Discussionmentioning
confidence: 87%
“…1) are tents with a series of stretchers and chairs for participants to sit/ lie while care is delivered. In common with other major mass participation events, the aims of care are to prevent a competitor's complaints from worsening, facilitate onward progression to collect belongings, and meet family/friends [37][38][39]. Additionally there are mechanisms to facilitate removal to hospital for those with more serious injuries and/or for those whose overall condition deteriorates.…”
Section: Activity Descriptionmentioning
confidence: 99%